From The History Of The Public Education System Of The Uzbek Ssr In The End Of The 20th Century - Mamasaidov Lutfillo Payzullo o‘g‘li (Periodica Journal, 2026)
This article analyzes the changes that occurred in the field of education in the late twentieth century in the Uzbek SSR, as well as the reforms implemented within the system during this period. It examines the process of students’ learning in schools, cases of school dropout, and the impact of cotton monoculture on educational policy, which led to the underdevelopment of school education or the slow growth in the number of schools relative to the population
Keywords: Education system; pedagogical staff; Pioneer